PEMETAAN PENGETAHUAN DAN TREN PENELITIAN EKONOMI SYARIAH: ANALISIS BIBLIOMETRIK TAHUN 2014-2024 - Solihin, Asep; Tanaya, Johan; Suhada, Wiwin (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to map the knowledge and trends of Islamic economics research during the period 2014–2024 using a bibliometric approach and the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. This process involves four stages: identification, screening, eligibility assessment, and inclusion, resulting in 320 articles from the Scopus database. Analysis was conducted to evaluate publication patterns, geographical distribution, author collaboration, and research themes and trends. The results show an increase in the number of annual publications with an average growth rate of 12.63%. Indonesia is the country with the largest contribution, followed by Malaysia and the United States, reflecting Southeast Asia's dominance in Islamic economics research. Frequently appearing keywords, such as Islamic Economics, Sharia Finance, and Knowledge Management, indicate the main focus of the research. Visualization using VOSviewer and Bibliosany identifies collaborative networks between authors and interrelated research themes.This study reveals that topics such as knowledge management, sustainability, and innovation are at the center of attention in Islamic economics research, with strong relevance to global challenges. This study is expected to be a strategic reference for academics, practitioners, and policy makers in determining future research priorities.